Effectiveness of Renal Denervation for Treatment of Resistant Hypertension: an Evidence-based Case Report - Minarma Siagian; Aldo Ferly; Arinna Irianti; Arky Kurniati; Florence Low; Ras A. Riza (Acta Medica Indonesiana, 2014)
Aim: to determine whether the renal sympathetic – nerve ablation method is more effective compared to multiple anti – hypertensive drug among patients with resistant hypertension. Methods: a search was conducted on PubMed. The selection of title and abstract was conducted using inclusion and exclusion criteria, which led to five relevant articles. The selected studies were critically appraised for its validity, importance and applicability. Results: one of studies showed that renal denervation is not effectively reduced blood pressure in patients with resistant hypertension; nevertheless other studies showed significant results. Conclusion: literature with strongest evidence showed that there is no relationship between renal sympathetic-nerve ablation procedure and reduction of blood pressure. However, as there is still some methodological flaw on the literature, we recommend doing another study that may find the appropriate results.